Sexual reproduction of the potentially cultivable sponge Mycale phyllophila (Porifera, Demospongiae). (23rd October 2015) - Huang, Dan; Ou, Huilong; Wang, Dexiang; Chen, Jun; Ding, Shaoxiong
Abstract : Sponges of the Mycale genus are an important source of several bioactive metabolites. The raw materials for studies on this genus mainly come from the wild populations. However, the scarce biomass of sponges in the wild has become an obstacle to the better investigation of the active substances. To establish aquaculture methods based on the sexual reproduction of the demosponge Mycale phyllophila and solve the sponge shortage problems, the sexual reproductive cycle of this species was studied. Our investigation is the first to report the sexual reproduction of the Mycale species in the coastal waters of China. We collected the sponge specimens from Dongshan Bay (Fujian, China) monthly from June 2012 to January 2014. Small samples of approximately 8 cm 3 in volume were cut from 15 sponges (10 tagged individuals and five random individuals) with surgical scissors for histological analysis. The results indicated that M. phyllophila is a hermaphroditic and viviparous species. The primary oocytes measured 30–50 μ m in diameter, while mature oocytes reached 300–400 µm by engulfing nearby nurse cells. Spermatic cysts containing asynchronous cells were found throughout the mesohyl, especially adjacent to the oscula. Macromeres in the middle and micromeres in the periphery were observed as the cleavage progressed. The reproductive activity of M. phyllophila lasted for 5–6 months and peaked when the average water temperature was above 25°C. This suggests that water temperature is an important environmental factor influencing the sexual reproduction cycle.